Co-occurrence of risky lifestyle behavior with overweight, excess abdominal fat and high blood pressure : case oriented approach - Vuletić, Silvije (Array, 2009)
Summary: The objective was to estimate the proportion of cases developed interim risk factors (INTF: overweight, excess abdominal fat, high blood pressure) in relation with behavioral risk factors (BEHF: smoking, heavy alcohol intake, unhealthy diet, physical inactivity). NOBIR group was defined as cases with no BEHF and BIR as those with them. Both groups show higher proportions of INTF in older age. The increase by age varies of twofold (overweight: 13.2–29.2 for men, 18.1–42.6 for women) to six fold (high blood pressure: 4.6–26.5 for men, 6.6–40.8 for women) in proportions. Women show higher proportions of INTF than men in both groups, but BIR group shows higher proportions than NOBIR in all the age groups taking the both gender together. As a BEHF the physical inactivity has a markedly increase with age (from 4% to more than 25%). Smoking is the only BEHF decreasing in oldest for all the INTF